(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article presents the results of field experimental studies carried out to investigate the influence of the installation height of the scraper (angle scraper) body relative to the center of rotation on the performance indicators of a disk plow. The installation height was varied from 0 to 15 cm at 5 cm intervals. The experiments aimed to determine the effect of the structural and technological parameters of the angle scraper on the operational efficiency of the disk plow. During the tests, the degree of soil pulverization, the completeness and depth of crop residue incorporation, the height of surface irregularities after plowing, and the specific draft resistance of the plow were analyzed. The obtained results provide an assessment of how the installation height of the angle scraper affects soil tillage quality and the overall energy efficiency of the plow’s operation.